Pressure-engineered structural and opestical properties of two-dimensional (C4H9NH3)2PbI4 perovskite exfoliated nm-thin flakes - Yin, Tingting (2020)
Resolving the structure–property relationships of two-dimensional (2D) organic–inorganic hybrid perovskites is essential for the development of photovoltaic and photoelectronic devices. Here, pressure (0–10 GPa) was applied to 2D hybrid perovskite flakes mechanically exfoliated from butylammonium lead halide single crystals, (C4H9NH3)2PbI4, from which we observed a series of changes of the strong excitonic emissions in the photoluminescence spectra. By correlating with in situ high-pressure X-ray diffraction results, we examine successfully the relationship between structural modifications in the inorganic PbI42– layer and their excitonic properties. During the transition between Pbca (1b) phase and Pbca (1a) phase at around 0.1 GPa, the decrease in ⟨Pb–I–Pb⟩ bond angle and increase in Pb–I bond length lead to an abrupt blue shift of the excitonic bandgap. The presence of the P21/a phase above 1.4 GPa increases the ⟨Pb–I–Pb⟩ bond angle and decreases the Pb–I bond length, leading to a deep red shift of the excitonic bandgap. The total band gap narrowing of ∼350 meV to 2.03 eV at 5.3 GPa before amorphization, facilitates (C4H9NH3)2PbI4 as a much better solar absorber. Moreover, phase transitions inevitably modify the carrier lifetime of (C4H9NH3)2PbI4, where an initial 150 ps at ambient phase is prolongated to 190 ps in the Pbca (1a) phase along with enhanced photoluminescence (PL), originating from pressure-induced strong radiative recombination of trapped excitons.The onset of P21/a phase shortens significantly the carrier lifetime to 53 ps along with a weak PL emission due to pressure-induced severe lattice distortion and amorphization. High-pressure study on (C4H9NH3)2PbI4 nm-thin flakes may provide insights into the mechanisms for synthetically designing novel 2D hybrid perovskite based photoelectronic devices and solar cells.